Vitamania : our obsessive quest for nutritional perfection - Price, Catherine, 1978- (The Penguin Press, 2015)
"The startling story of America's devotion to vitamins-and how it keeps us from good health Health-conscious Americans seek out vitamins any way they can, whether in a morning glass of orange juice, a piece of vitamin-enriched bread, or a daily multivitamin. We believe that vitamins are always beneficial and that the more we can get, the better-and yet despite this familiarity, few of us could explain what vitamins actually are. Instead, we outsource our questions to experts and interpret "vitamin" as shorthand for "health." What we don't realize-and what Vitamania reveals-is that the experts themselves are surprisingly short on answers. Yes, we need vitamins; without them, we would die. Yet despite a century of scientific research (the word "vitamin" was coined only in 1912), there is little consensus around even the simplest of questions, whether it's exactly how much we each require or what these thirteen dietary chemicals actually do. The one thing that experts do agree upon is that the best way to get our nutrients is in the foods that naturally contain them, which have countless chemicals beyond vitamins that may be beneficial. But thanks to our love of processed foods (whose natural vitamins and other chemicals have often been removed or destroyed), this is exactly what most of us are not doing. Instead, we allow marketers to use the addition of synthetic vitamins to blind us to what else in food we might be missing, leading us to accept as healthy products that we might (and should) otherwise reject. Grounded in history-but firmly oriented toward the future-Vitamania reveals the surprising story of how our embrace of vitamins led to today's Wild West of dietary supplements and investigates the complicated psychological relationship we've developed with these thirteen mysterious chemicals. In so doing, Vitamania both demolishes many of our society's most cherished myths about nutrition and challenges us to reevaluate our own beliefs. Impressively researched, counterintuitive, and engaging, Vitamania won't just change the way you think about vitamins. It will change the way you think about food. "--